Coffee drink consumption pattern and its contribution of calcium and caffeine intake related to bone status in college students in Korea - Choi, In-Young; Kim, Mi-Hyun (Progress in Nutrition, 2023)
Background and aim: Coffee consumption is steadily increasing especially among young adults in Korea. This study aimed to investigate the coffee drink consumption and its association with calcium and caffeine intake related to bone in young adults. Methods: A total of 145 male and 156 female college students aged 19–29 years participated in the study. Anthropometric measurements and a questionnaire survey were conducted. Bone mineral density (BMD) of the calcaneus was measured using quantitative ultrasound. The study participants were divided into three groups according to their coffee consumption status: high–coffee group (HC≥median of daily intake), low coffee group (LC<median of daily intake), and non-coffee group. Results: The average daily intake of any type of coffee was 2.72 servings for men and 1.72 servings for women in the HC, and 0.59 servings for men and 0.43 servings for women in the LC. The average calcium intake from coffee drinks was 147.54 mg/day for men and 85.31 mg/day for women in the HC, and 59.83 mg/day for men and 41.30 mg/day for women in the LC. The average caffeine intake from coffee was 301.02 mg/day for men and 190.15 mg/day for women in the HC, and 64.42 mg/day for men and 42.84 mg/day for women in the LC. The type of coffee contributing the most to calcium intake was café-made latte. Café-made black coffee contributed the most to caffeine intake. After adjusting for age, BMI, smoking, exercise, and drinking, there were no significant differences in BMD of the calcaneus among the three groups. Conclusions: The intake levels of calcium and caffeine varied greatly in the college students. Although coffee consumption amount and pattern may affect bone metabolism in the long term, significant differences in BMD were not found in this study.